Clinical and Therapeutic Characteristics in Patients with Chronic Kidney Disease presenting with Acute Coronary Syndrome - Shah, Nischal; Gajurel, Ratna Mani; Poudel, Chandra Mani; Ghimire, Roshan; Yadav, Sutap (Nepalese Heart Journal, 2022)
Background and Aims: The prevalence of chronic kidney disease (CKD) and coronary artery disease (CAD) is increasing in Nepal. Chronic inflammation, metabolic and uremic effect of CKD along with traditional cardiovascular (CV) risk factor makes CV disease common and unique in these patients. Even with advancement in treatment, acute coronary syndrome (ACS), there is tendency towards lower rates of evidence-based therapies. This study was conducted with an aim to know clinical profile and the management strategy of CKD patient presenting with ACS. Methods: Single-centered, cross-sectional study carried out in, Manmohan Cardiothoracic and Vascular Transplant Centre, Kathmandu from July 2021 to December 2021. Of total 68 patient with ACS and CKD, history, physical examination, laboratory investigations along with electrocardiogram, echocardiography and coronary angiogram, were critically assessed. Results: Out of total 68 patients, 47 (69.1%) were male. In CKD patient presenting with ACS, predominant age group involved was 51-60 years (27.9%) with the mean age of 61.4 years. Out of them, 34 (50%) were in stage 5 with 32 (47.1%) already on maintenance hemodialysis. Average serum creatine and creatine clearance was 5.84 mg/dl and 16.29 mL/min/1.73m2 respectively. Smoking, diabetes and hypertension were common occurring in 39 (57.4%), 49 (72.1%) and 57 (83.8%) of all CKD patient respectively. Among them, 61 (89.7%) underwent angiography in which 23 (37.7%) had triple vessel disease. Percutaneous intervention was done for 38 (55.9%) patients and 13 (19.1%) were referred for coronary artery bypass graft (CABG). Conclusion: Traditional risk factor and multivessel involvement were common in CKD patient presenting with ACS and there less tendency to undergo revascularization procedure, especially with advancing age in the studied population.